Acceptability of using standing orders to deliver human papillomavirus vaccines in the outpatient obstetrician/gynecologist setting. Issue 15 (8th April 2015) - Dempsey, Amanda F.; Pyrzanowski, Jennifer; Brewer, Sarah; Barnard, Juliana; Sevick, Carter; O'Leary, Sean T.
Highlights Half (53%) of the women surveyed agree with the idea of using standing orders for HPV vaccination. However, personal acceptance of getting the vaccine using standing orders was lower (40%). Acceptance was higher for HPV series completion than initiation, and for adults than adolescents.